The language games of virtual communities: The case of a Romanian expatriate forum. Issue 1 (1st June 2019) - Gradinaru, Camelia
This article assesses the relevance of Wittgenstein's late philosophy for the study of online forms of communication. In particular, the article deals with the appropriateness of using the concept of language game for the purpose of describing what happens in a virtual community. Testing Wittgenstein's concept of language game in online context, we also analyse the language practices of one specific virtual community (patterns of communication, style, roles of members, internal organization of this 'form of life').